Redesign of venting machine to reduce scrap defect crease in tires manufacture company - Fajar Abdul Aziz; Subekti Subekti (JTTM : Jurnal Terapan Teknik Mesin, 2024)
An apparatus for venting or perforating green tires in order to release trapped air is known as a-venting machine. Productivity will drop in May and July of 2023 as a result of scrap issues brought on by green tire defect creases. The term "defect crease" refers to a flaw in which the operator's manual hand rotation causes silicon to adhere to the side or tread ending of the green tire. Modifications were made with the intention of reducing scrap brought on by defect creases in order to lessen this issue. In order to eliminate the need for the operator to manually rotate the green tire, the roll driver that was initially fixed was replaced with one that can rotate automatically. The scrap defect decrease was 93.15% lower as a result of the modification, going from 73 ppm in the May–July 2023 period to 5 ppm in the September–November 2023 period